TINJAUAN TERHADAP RATIO DECIDENDI HAKIM PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI SAMARINDA DALAM PERKARA PEMUTUSAN HUBUNGAN KERJA BURUH PT.SIMS JAYA KALTIM DI KABUPATEN PASER - Neneng Herawati (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT       Termination of Employment is a type of industrial relations dispute regulated in Act Number 13 of 2003 and Act Number 2 of 2004. Termination of Employment occurs when there are violations committed by workers in the Labor Law, Collective Labor Agreement, and Regulations Company. Or conversely there is also termination of employment done by companies against their workers. Termination of employment in this case was filed by the company on the grounds of inviting or influencing others to strike. . In the trial both based on the evidence and witnesses the reasons for the lawsuit were not proven, but even though based on the evidence and witnesses were not proven, the Panel of Judges granted the Plaintiff's claim by stating that the employment relationship between the Plaintiff and Defendant was terminated on the grounds that the employment relationship was not harmonious.This type of research used in this paper the author uses normative juridical research methods, namely "legal research conducted by examining library material or secondary data as a basic material to be investigated by conducting a search of the regulations and literature relating to the problem under study ".       After the author conducted the research there are the following results: that the judge in deciding this case was not based on the principle of evidence contained in the trial but the panel of judges decided the case based on legal considerations based on considerations between the plaintiff and the defendant not in harmony even though the reason for termination of employment based on employment relations that are not harmonious, not regulated in Law Number 13 of 2003, concerning employment or in Act Number 2 of 2004, settlement of industrial relations disputesKeywords: Decidendi Ratio, Industrial Relations, Labor.